Virucidal effects of eucalyptus essential oil on porcine reproductive and respiratory syndrome virus - Chen, Tianbao; Liu, Baoling; Liu, Dingyu; Luo, Qin; Wang, Yani; Wang, Xiaohu; He, Dongsheng; Cai, Rujian (Frontiers in Microbiology, 2024)
Currently, the efficacy of vaccination for preventing and controlling PRRSV is insufficient. Therefore, there is an urgent need for novel effective preventive strategies. This study aimed to investigate the antiviral effect of Eucalyptus essential oil (EEO) against PRRSV in vitro. Marc-145 cells were infected with PRRSV (rJXA1-R), and the toxicity of EEO in the cells was measured using the Cell Counting Kit-8 method. Additionally, the antiviral effect of EEO on PRRSV-infected cells was assessed using three treatment methods: drug administration post-PRRSV inoculation (posttreatment), drug administration before PRRSV inoculation (pre-treatment), and simultaneous drug administration and PRRSV inoculation (co-treatment). The EEO could not inhibit virus adsorption and/or replication since post-treatment and pre-treatment did not prevent viral infectivity. However, EEO exerted a significant virucidal effect on PRRSV. When PRRSV-infected cells were treated with 0.0156%, 0.0312%, and 0.0625% EEO, the cell survival rates were 55.37%, 118.96%, and 121.67%, respectively, and the titer of progeny virions decreased from 5.77 Log10TCID50 to 5.21 Log10TCID50, 0.55 Log10TCID50, and less than 0.167 Log10TCID50, respectively (where TCID50 is the 50% tissue culture infected dose). The fluorescence intensity of the PRRSV N protein significantly decreased in the indirect immunofluorescence assay. When cells were co-treated with EEO (0.0625%) and PRRSV (1000 TCID50) for 15 min, the viral particles were inactivated, and PRRSV (1000 TCID50) particles loss infectivity when the co-treatment time reached 60 min. In a word, EEO has no obvious therapeutic effect on PRRSV infection, but it can effectively inactivate virus particles and make them lose the ability to infect cells. These findings provide insights for the development and use of EEO to treat PRRS.